2007
DOI: 10.1111/j.1464-410x.2007.07193.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence imaging to monitor bladder cancer cell adhesion in vivo: a new approach to optimize a syngeneic, orthotopic, murine bladder cancer model

Abstract: OBJECTIVE To improve the orthotopic murine bladder cancer model by using bioluminescent (BL) MB49 tumour cells for noninvasive in vivo monitoring of tumour growth and to examine the efficacy of integrin receptor‐blocking oligopeptides on preventing tumour cell adhesion in this improved bladder cancer model. MATERIALS AND METHODS The capacity of oligopeptide combinations to interfere with tumour cell adhesion was assessed in vivo in a syngeneic, orthotopic, murine bladder cancer model. Tumour outgrowth was moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…1B) due to presence of necrotic tumors and/or low tumor-perfusion, preventing tumor-penetration of the injected luciferin. 13 A classical schedule for intravesical treatment in this model start 1 day after tumor implantation and is given four-times once a week. 12 The first intravesical instillation results in an initially delayed tumor-growth (see tumor bioluminescence at day 8 in Fig.…”
Section: Intravesical Ty21a Induces Bladder-tumor Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) due to presence of necrotic tumors and/or low tumor-perfusion, preventing tumor-penetration of the injected luciferin. 13 A classical schedule for intravesical treatment in this model start 1 day after tumor implantation and is given four-times once a week. 12 The first intravesical instillation results in an initially delayed tumor-growth (see tumor bioluminescence at day 8 in Fig.…”
Section: Intravesical Ty21a Induces Bladder-tumor Regressionmentioning
confidence: 99%
“…Tumor growth was monitored by bioluminescence 15 min after intraperitoneal injection of D-luciferin (Promega, 150 mg/g of body weight) in the Xenogen imaging system (Xenogen/IVIS Caliper Life Science, kindly provided by cellular imaging facility, CIF/UNIL, Lausanne, Switzerland). Bioluminescence monitoring of MB49-luc tumor is very efficient for assessing tumor establishment and growth during the first 3 weeks, however, uncontrolled loss of luminescence of the growing tumors can then often appear, 13 requiring additional monitoring by palpation, hematuria and overall health status of the mice, that were euthanized in case of >15% weight-loss.…”
Section: The Mb49 Orthotopic Bladder Tumor Modelmentioning
confidence: 99%
“…Therefore, bioluminescence imaging mainly can be used as a qualitative technique with limitations in the quantification of more advanced tumor stages. 29 In our study light emissions over ROIs were used only to analyze tumor development of one and the same animal before and after treatment (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Re-seeding may be facilitated, in part, by the interaction of tumor cell integrins with extracellular matrix (ECM) components including fibronectin, laminin, and collagen, all of which are likely to be exposed at the surgical site following resection. Previous reports have indicated that specific mammalian integrins, particularly integrin heterodimer family members alpha3beta1 (α3β1) and alpha5beta1 (α5β1), are implicated as being required for the attachment of tumor cells to the ECM and establishment of tumors in the urothelium in vivo (11)(12)(13).…”
Section: Been Previously Characterized As An Integrin-specific Oncolymentioning
confidence: 99%